Integrasi Filosofi Pendidikan Ki Hadjar Dewantara, Profil Pelajar Pancasila, Dan Nilai Kekristenan - Hendra Gunawan Parulian; Mangatur Parsaoran Simbolon; Rudy Harto Siringoringo (Journal on Education, 2025)
This article examines the integration between Ki Hadjar Dewantara's educational philosophy, the Pancasila Student Profile, and Christian values ​​as a holistic approach to education in Indonesia. Ki Hadjar Dewantara's philosophy emphasizes the importance of Tri-Nga (understand, feel, act) and Tri-Center of Education (family, school, community), which is in line with the dimensions of the Pancasila Student Profile. This approach strengthens students' spiritual, intellectual and social character. Christian values ​​such as love, justice, and service add depth to the moral dimension of education. This article concludes that this integration provides a new direction in Indonesian education, creating a generation that is not only intellectually intelligent, but also highly moral and globally competitive.